Chloro‐Bridged Hexanuclear Pd(II) Clusters Supported by cis‐Blocking Tris(imido)phosphate Trianions. Issue 33 (22nd November 2017) - Gupta, Arvind K.; Reddy, Shada Arun Dixith; Rajasekar, Prabhakaran; Prakash, Prabhat; Boomishankar, Ramamoorthy
Abstract: Transition metal complexes derived from anionic polyimido ligands are very limited in the literature. Here we describe the deprotonation of alkyl substituted phosphoric triamides with bis(benzonitrile)palladium dichloride which results in the formation of chloro‐bridged hexanuclear palladium(II) clusters of formula Pd3 [(NR)3 PO](Cl)3 2 in octahedral and prismatic geometries. These clusters consist of two trinuclear Pd3 ‐motifs, each cis ‐protected by a tris(alkylimido)phosphate trianion, which are linked together by six μ2 ‐Cl bridges. A staggered arrangement of the two imido‐Pd3 units results in the formation of octahedral clusters (R= i Bu, n Bu, c Hex, i Pr and n Pr), while an eclipsed conformation (R= t Bu) gives rise to a prismatic cluster. A similar prismatic configuration was obtained for the mixed‐bridged clusters Pd3 [(NR)3 PO](OAc)2 (Cl)2 (R= c Hex and i Pr), formed in the reaction involving the corresponding phosphoric triamide, Pd(OAc)2 and Pd(PhCN)2 Cl2 . The reaction of an octahedral cluster Pd3 [(N n Pr)3 PO](Cl)3 2 with 1, 1'‐ferrocene dicarboxylic acid (FDC−H) gave the prismatic cluster Pd3 [(N n Pr)3 PO](FDC)(Cl)2 which again consists of a mixed‐bridged environment with FDC and Cl − linkers. Further, treatment of the octahedral Pd3 [(N n Pr)3 PO](Cl)3 2 cluster with i PrNH2, a stronger nucleophile, leads to its symmetric cleavage and forms the trinuclear cluster Pd3 [(NR)3 PO]Cl3 (R'NH2 )3 . We have also shown the catalytic activity of some of these Pd(II) complexes in the Suzuki reactions in both organic and aqueous phase conditions which suggest that all these imido‐Pd(II) clusters are still suitable for catalytic reactions. Abstract : Carefully Clustered: Octahedral and Prismatic chloro‐bridged Pd(II) clusters were synthesized by the deprotonation of Phosphoric triamides with Pd(PhCN)2 Cl2 . The hexanuclear clusters were sandwiched between two tris(imido)phosphate trianions. The reactivity studies of these clusters with certain organic acid and amine functionalities reveal the stability of the imido‐Pd3 motifs. Performing Suzuki coupling reactions with these clusters demonstrated their utility as efficient catalysts.